Negative electrode for secondary battery and method for producing same
By using a laminated structure of a carbonaceous current collector and a porous polymer layer and a lithium-based material layer in a lithium secondary battery, the problems of high reactivity and low rigidity of the lithium metal negative electrode are solved, and the stability and life of the battery are improved.
Patent Information
- Application Number
- CN202380037426.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing lithium secondary batteries, the lithium metal negative electrode increases the electrode thickness, deteriorates the cycle characteristics and safety, and is difficult to manufacture due to high reactivity and low rigidity.
A laminated structure of a carbonaceous current collector, a porous polymer layer and a lithium material layer is adopted, and a negative electrode is formed through the pressing process. The lithium material layer includes lithium metal and a lithium alloy, and through holes are formed in the porous polymer layer to improve adhesion.
It improves the rigidity, tensile strength and elongation of the negative electrode, improves the stability and cycle life of the battery, reduces the energy density of the single cell, and extends the battery life.
Smart Images

Figure CN119137762A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode for a secondary battery and a method for manufacturing the same. In particular, the present disclosure relates to a negative electrode for a secondary battery having excellent rigidity and lithium plating ability, and a method for manufacturing the same.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0110407 filed on August 31, 2022 and Korean Patent Application No. 10-2022-0187919 filed on December 28, 2022, the disclosures of which are incorporated herein by reference. Background Art
[0003] Recently, energy storage technology has received increasing attention. As the application of energy storage technology expands to the energy source of mobile phones, portable cameras and notebook personal computers, and even the energy source of electric vehicles, more and more efforts have been invested in the research and development of electrochemical devices. In this context, electrochemical devices have received the most attention, and the development of rechargeable secondary batteries has become the focus of attention. Recently, in order to improve the capacity density and specific energy in the development of such batteries, research and development of designing new electrodes and batteries has been carried out.
[0004] Among commercially available secondary batteries, lithium secondary batteries developed in the early 1990s have attracted attention because of their higher operating voltage and significantly higher energy density than conventional batteries such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries using aqueous electrolytes.
[0005] Among such secondary batteries, lithium sulfur (LiS) batteries with high energy density have attracted attention as next-generation secondary batteries that can replace lithium ion batteries. Lithium sulfur batteries use sulfur-based materials as positive electrode active materials. In lithium sulfur batteries, sulfur reduction and lithium metal oxidation occur during discharge, where sulfur forms lithium polysulfides (Li2S2, Li2S4, Li2S6, Li2S8) with linear structures from S8 with a ring structure. Such lithium sulfur batteries are characterized in that they show a step-type discharge voltage until the polysulfide (PS) is completely reduced to Li2S.
[0006] Metallic lithium can be used for the negative electrode of lithium secondary batteries. However, when lithium metal is used as the negative electrode, due to the high reactivity of lithium, it exhibits high reactivity with the electrolyte during charge / discharge, and as the charge / discharge cycle is repeated, dendrites are formed on the negative electrode surface, resulting in problems such as increased electrode thickness and deterioration of cycle characteristics and safety. Another problem is that it is difficult to manufacture a negative electrode from lithium metal due to its low rigidity. Summary of the invention
[0007] Technical issues
[0008] The present disclosure is intended to solve the problems of the related art, and therefore, the present disclosure is directed to providing a negative electrode for a secondary battery having improved elongation, rigidity, and safety, a method for manufacturing the same, and a secondary battery including the same.
[0009] Technical Solution
[0010] In one aspect of the present disclosure, there is provided a negative electrode for a secondary battery according to any one of the following embodiments.
[0011] According to a first embodiment of the present disclosure, there is provided a negative electrode for a secondary battery, the negative electrode comprising:
[0012] a carbonaceous current collector; a porous polymer layer disposed on at least one surface of the carbonaceous current collector; and a lithium-based material layer disposed on an upper surface of the porous polymer layer.
[0013] According to a second embodiment of the present disclosure, there is provided the negative electrode for a secondary battery as defined in the first embodiment, wherein the lithium-based material layer contains at least one of lithium metal and a lithium alloy.
[0014] According to a third embodiment of the present disclosure, there is provided the negative electrode for a secondary battery as defined in the first or second embodiment, wherein the lithium-based material layer is a lithium metal layer.
[0015] According to a fourth embodiment of the present disclosure, there is provided a negative electrode for a secondary battery as defined in any one of the first to third embodiments, wherein at least one through-hole is formed in the porous polymer layer, and the carbonaceous current collector and the lithium-based material layer are attached to each other through the through-hole.
[0016] According to a fifth embodiment of the present disclosure, there is provided the secondary battery negative electrode as defined in the fourth embodiment, wherein the through holes formed in the porous polymer layer occupy an area equivalent to 10% to 90% relative to the total area of the porous polymer layer.
[0017] According to a sixth embodiment of the present disclosure, there is provided the negative electrode for a secondary battery as defined in the third or fourth embodiment, wherein the diameter of the through-holes formed in the porous polymer layer is 0.5 to 3 cm.
[0018] According to a seventh embodiment of the present disclosure, there is provided the negative electrode for a secondary battery as defined in any one of the first to sixth embodiments, wherein the porous polymer layer is provided on both surfaces of the carbonaceous current collector.
[0019] According to an eighth embodiment of the present disclosure, there is provided a negative electrode for a secondary battery as defined in any one of the first to seventh embodiments, wherein the specific surface area of the carbonaceous current collector is 50 m 2 / g or above.
[0020] According to a ninth embodiment of the present disclosure, there is provided a negative electrode for a secondary battery as defined in any one of the first to eighth embodiments, wherein the surface density of the carbonaceous current collector is 100 g / m 2 the following.
[0021] According to the tenth embodiment of the present disclosure, a negative electrode for a secondary battery as defined in any one of the first to ninth embodiments is provided, wherein the carbonaceous current collector layer comprises graphite, graphene, carbon nanotubes (CNTs), graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), or two or more thereof.
[0022] According to an eleventh embodiment of the present disclosure, there is provided a negative electrode for a secondary battery as defined in any one of the first to tenth embodiments, wherein the porous polymer layer comprises polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, polyethylene naphthalate, or two or more thereof.
[0023] In another aspect of the present disclosure, there is provided a method of manufacturing a negative electrode for a secondary battery according to any one of the following embodiments.
[0024] According to the twelfth embodiment of the present disclosure, a method for manufacturing a negative electrode for a secondary battery is provided, the method comprising the following steps: stacking a carbonaceous current collector, a porous polymer layer having at least one through-hole on at least one surface of the carbonaceous current collector, and a lithium-based material layer on the upper surface of the porous polymer layer to form a stack; and compressing the stack through a pressing process.
[0025] According to a thirteenth embodiment of the present disclosure, there is provided the method of manufacturing a negative electrode for a secondary battery as defined in the twelfth embodiment, wherein the lithium-based material layer contains at least one of lithium metal and a lithium alloy.
[0026] According to a fourteenth embodiment of the present disclosure, there is provided the method of manufacturing a negative electrode for a secondary battery as defined in the twelfth or thirteenth embodiment, wherein the lithium-based material layer is a lithium metal layer.
[0027] According to a fifteenth embodiment of the present disclosure, there is provided the method of manufacturing a negative electrode for a secondary battery as defined in any one of the twelfth to fourteenth embodiments, wherein the compressing step is performed at a temperature of 180° C. or lower.
[0028] According to the sixteenth embodiment of the present disclosure, a method for manufacturing a negative electrode for a secondary battery as defined in any one of the twelfth to fifteenth embodiments is provided, wherein in the compression step, the lithium-based material layer and the carbonaceous current collector are attached to each other through through holes formed in the porous polymer layer.
[0029] According to still another embodiment of the present disclosure, a secondary battery according to the following embodiments is provided.
[0030] According to a seventeenth embodiment of the present disclosure, there is provided a secondary battery including: a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte, wherein the negative electrode is the negative electrode as defined in any one of the first to eleventh embodiments.
[0031] Beneficial Effects
[0032] According to one embodiment of the present disclosure, the rigidity of a negative electrode for a secondary battery can be improved. In particular, the present disclosure provides a negative electrode for a secondary battery having improved stability, tensile strength, and elongation.
[0033] In addition, according to one embodiment of the present disclosure, a negative electrode uniformly plated with a lithium-based material may be provided.
[0034] In addition, according to one embodiment of the present disclosure, the life of the negative electrode can be improved.
[0035] Furthermore, a secondary battery including the negative electrode for a secondary battery shows an improvement in cycle life.
[0036] In addition, the present disclosure may have various other effects which will be described in each embodiment, or effects which can be easily inferred by those skilled in the art will be omitted. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the foregoing disclosure, are used to provide a further understanding of the technical features of the present disclosure. Therefore, the present disclosure is not to be construed as being limited to the accompanying drawings.
[0038] Figure 1 is a schematic cross-sectional view showing a negative electrode for a secondary battery according to one embodiment of the present disclosure.
[0039] Figure 2is a schematic cross-sectional view showing a negative electrode for a secondary battery according to one embodiment of the present disclosure.
[0040] Figure 3 is a graph showing the results of a tensile strength test of one example of the present disclosure.
[0041] Figure 4 It is a graph showing the tensile strength test results of Comparative Examples of the present disclosure.
[0042] Figure 5 Graphs showing single cell performance test results of an example of the present disclosure and a comparative example. DETAILED DESCRIPTION
[0043] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms used in the specification and the appended claims should not be interpreted as limited to the general and dictionary meanings, but should be interpreted based on the meanings and concepts corresponding to the technical aspects of the present disclosure on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation.
[0044] Therefore, the descriptions presented herein are merely preferred examples for illustrative purposes, and are not intended to limit the scope of the present disclosure, and it should be appreciated that other equivalent substitutions and modifications may be made thereto without departing from the scope of the present disclosure.
[0045] It will also be understood that the terms “comprise” and / or “including”, “include” and / or “comprising”, or “have” and / or “having” when used in the present specification do not exclude the presence of other elements, but indicate the presence of other elements unless otherwise stated.
[0046] In one aspect of the present disclosure, a negative electrode for a secondary battery is provided, the negative electrode comprising: a carbonaceous current collector; a porous polymer layer disposed on at least one surface of the carbonaceous current collector; and a lithium-based material layer disposed on an upper surface of the porous polymer layer.
[0047] According to the prior art, lithium metal itself or a laminate of lithium metal and a current collector such as copper foil has been used as a negative electrode for a secondary battery. However, when lithium metal is used alone as a negative electrode, there is a problem that the negative electrode is fragile and shows low rigidity.
[0048] According to the present disclosure, the elastic force and tensile strength of the negative electrode can be improved and the processability and processability of the negative electrode can be improved by using a carbonaceous current collector for the negative electrode. In addition, since a carbonaceous material with current collection capability is additionally used compared to a lithium metal foil negative electrode using lithium metal itself according to the prior art, the discharge capacity of the single cell can be improved and the coulombic efficiency of the single cell can be stabilized. In addition, since the carbonaceous current collector is lighter than the conventional copper foil current collector, the reduction in energy density of the single cell caused by the introduction of the current collector can be significantly reduced.
[0049] In addition, according to the present disclosure, the elongation and elastic force of the negative electrode can be further improved by using a porous polymer layer for the negative electrode. The side reaction between the carbonaceous current collector and the electrolyte can also be prevented by inhibiting the contact between the carbonaceous current collector and the bulk electrolyte. In this way, the life of the battery can also be improved.
[0050] In addition, the tensile strength and elongation can be improved by using a porous polymer layer for the negative electrode. In addition, since the tensile strength and elongation of the negative electrode are improved, the life of the negative electrode and the capacity of the secondary battery can be improved and the stability can be improved.
[0051] According to one embodiment of the present disclosure, the porous polymer layer may be disposed on at least one side of the carbonaceous current collector, in particular, on at least one surface of the carbonaceous current collector. In addition, the lithium-based material layer may be disposed on the upper side of the porous polymer layer, in particular, on at least the upper surface of the porous polymer layer.
[0052] Figure 1 is a schematic cross-sectional view showing a negative electrode 10 for a secondary battery according to one embodiment of the present disclosure.
[0053] Reference Figure 1 , the porous polymer layer 200 is disposed on both surfaces of the carbonaceous current collector 100. In addition, the lithium-based material layer 300 is disposed on the upper surface of each porous polymer layer 200.
[0054] According to one embodiment of the present disclosure, when the porous polymer layer is disposed on at least one surface of the carbonaceous current collector, the porous polymer layer may be disposed on the entire surface of one surface of the carbonaceous current collector or on a portion of one surface of the carbonaceous current collector.
[0055] According to one embodiment of the present disclosure, the porous polymer layer may be disposed on at least one surface or at least one side of the carbonaceous current collector while being in direct contact with the carbonaceous current collector, but other layers may be disposed in part or all between the porous polymer layer and the carbonaceous current collector. For example, lithium metal may be disposed between the carbonaceous current collector and the porous polymer layer.
[0056] The lithium-based material layer can be disposed on the upper side of the porous polymer layer, and in particular, can be disposed on the upper surface of the porous polymer layer. More particularly, since the carbonaceous current collector is disposed on the lower surface of the porous polymer layer, the lithium-based material layer can be disposed on the upper surface of the porous polymer layer.
[0057] For example, when the porous polymer layer is disposed on one surface of the carbonaceous current collector, the carbonaceous current collector, the porous polymer layer and the lithium-based material layer may be stacked in sequence. In addition, when the porous polymer layer is disposed on both surfaces of the carbonaceous current collector, the first lithium-based material layer, the first porous polymer layer, the carbonaceous current collector, the second porous polymer layer and the second lithium-based material layer may be stacked in sequence.
[0058] In addition, the lithium-based material layer may be provided on the entire upper surface of the porous polymer layer, or may be provided on a portion of the upper surface of the porous polymer layer.
[0059] According to one embodiment of the present disclosure, the lithium-based material layer includes at least one of lithium metal and lithium alloy. The lithium-based material layer may be a lithium alloy layer or a lithium metal layer. The lithium alloy includes an element capable of forming an alloy with lithium. Here, the element capable of forming an alloy with lithium may include Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, Al or an alloy thereof.
[0060] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, the porous polymer layer may have at least one through-hole formed therein.
[0061] The negative electrode for a secondary battery according to the present disclosure may have a structure in which the carbonaceous current collector, the porous polymer layer and the lithium-based material layer are stacked in sequence. Here, the adhesion between the carbonaceous current collector used according to the present disclosure and the lithium-based material layer may be higher than the adhesion between the porous polymer layer and the lithium-based material layer. Therefore, in order to further improve the adhesion of the stack, at least one through hole may be formed in the porous polymer layer so that the carbonaceous current collector can directly contact the lithium-based material layer through the through hole.
[0062] In addition, as described above, the lithium-based material layer and the carbonaceous current collector may be in direct contact with each other through the through-holes, but the through-holes disclosed herein should be distinguished from pores formed in the porous polymer layer itself.
[0063] The porous polymer layer itself has holes, and at least one hole may run through a surface of the porous polymer layer so that the surface can be interconnected with another surface of the porous polymer layer. However, such a hole may not be formed with the shortest path from one surface of the porous polymer layer to another surface thereof, but may be passed from one surface of the porous polymer layer to another surface thereof through a complex path. Therefore, it is difficult to make the lithium-based material layer and the carbonaceous current collector directly contact each other through the holes formed in the porous polymer layer itself. On the contrary, the through hole according to the present disclosure can be separately run through and formed in the porous polymer layer so that the lithium-based material layer and the carbonaceous current collector layer can directly contact each other.
[0064] Figure 2 is a schematic cross-sectional view showing a negative electrode 10 for a secondary battery according to one embodiment of the present disclosure. Figure 2 , a porous polymer layer 200 having through-holes 210 therein is provided on at least one surface of a carbonaceous current collector 100, and a lithium-based material layer 300 is provided on an upper surface of the porous polymer layer having through-holes 210 therein, thereby forming a laminate. In this way, the lithium-based material layer 300 and the carbonaceous current collector 100 can be directly contacted and attached to each other through the through-holes 210 formed in the porous polymer layer 200, so that the interlayer adhesion of the laminate can be well maintained.
[0065] In a negative electrode for a secondary battery according to an embodiment of the present disclosure, a through hole formed in the porous polymer layer may be perpendicular to the porous polymer layer. When the through hole is perpendicular to the porous polymer layer, the lithium-based material layer may be more effectively in contact with the carbonaceous current collector. However, the through hole formed in the porous polymer layer is not limited to the above-mentioned embodiment, and any through hole formed in a manner that allows the lithium-based material layer and the carbonaceous current collector layer to effectively contact each other through the through hole may be allowed.
[0066] In a negative electrode for a secondary battery according to an embodiment of the present disclosure, the diameter of the through hole formed in the porous polymer layer may be greater than the diameter of the hole formed in the porous polymer layer. For example, the diameter of the through hole may be 0.5-3.0 cm, or 1.0-2.0 cm. When the diameter of the through hole falls within the above-defined range, the lithium-based material layer and the carbonaceous current collector may be attached to each other through the through hole while achieving a sufficient level of adhesion.
[0067] Preferably, the through hole may have a circular shape. However, the shape of the through hole is not limited to a circular shape, but may be formed in various shapes, including a quadrilateral shape, a triangular shape, etc. When the through hole does not have a circular shape, the distance between the center of the through hole and the farthest point therefrom may be 0.25-1.5 cm.
[0068] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, the through holes may be formed in the porous polymer layer at intervals of 0.5-1.5 cm. When the intervals of the through holes satisfy the above-defined range, the lithium-based material layer and the carbonaceous current collector may be attached to each other while achieving a sufficient level of adhesion.
[0069] In a negative electrode for a secondary battery according to an embodiment of the present disclosure, the through-holes may occupy 15%-60% or 20%-40% of the area relative to the total area of the porous polymer layer. When the area occupied by the through-holes satisfies the above-defined range relative to the total area of the porous polymer layer, the tensile strength and elongation of the negative electrode can be improved while providing a negative electrode laminate with improved interlayer adhesion, and the negative electrode maintains an appropriate level of elastic force and rigidity. The total area refers to the total surface area when the porous polymer layer is observed from the upper side, and may even cover an area including the area occupied by the through-holes of the porous polymer layer.
[0070] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, the porosity of the porous polymer layer may be 40%-70%. When the porosity satisfies the above-defined range, ion conduction can be smoothly completed through the porous polymer layer, thereby ensuring a sufficient level of ion conductivity.
[0071] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, the specific surface area of the carbonaceous current collector may be 30 m 2 / g or more, 50 m 2 / g or more, 80 m 2 / g or above or 100 m 2 / g or more, and can be 2000 m 2When the specific surface area of the carbonaceous current collector satisfies the above-defined range, it is possible to ensure a surface area capable of fully supporting the lithium negative electrode and reduce the current density per unit area, thereby providing advantages in stabilizing lithium or lithium plating.
[0072] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, the surface density of the carbonaceous current collector may be 100 g / m 2 Below, 70 g / m 2 Below, 50 g / m 2 Below, 30 g / m 2 Below, 15 g / m 2 Below or 8 g / m 2 Below, and can be 0.1 g / m 2 When the surface density of the carbonaceous current collector satisfies the above-defined range, the reduction in single cell energy density caused by the introduction of the current collector can be reduced. The surface density refers to the value obtained by dividing the weight of the carbonaceous current collector by its surface area (i.e., external area) assuming that there are no pores in the carbonaceous current collector.
[0073] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, the thickness of the carbonaceous current collector may be 3-20 μm, or 5-12 μm. When the thickness of the carbonaceous current collector satisfies the above-defined range, the negative electrode for a secondary battery according to the present disclosure may be provided with an appropriate level of elongation, rigidity, and elastic force.
[0074] In the negative electrode for secondary batteries according to one embodiment of the present disclosure, the carbonaceous current collector may include graphite, graphene, carbon nanotubes (CNT), graphite nanofibers (GNF), carbon nanofibers (CNF), activated carbon fibers (ACF), or two or more thereof. However, the carbonaceous current collector is not limited to the examples listed above, but any conventional carbonaceous material can be used as the carbonaceous current collector according to the present disclosure.
[0075] In a negative electrode for a secondary battery according to an embodiment of the present disclosure, the carbonaceous current collector may have a porous structure in which a carbonaceous material is entangled. For example, the carbonaceous current collector may have a porous carbon nanotube composite structure formed by the entanglement of carbon nanotube chains. In addition, the carbonaceous current collector may be a mat-type current collector that forms a self-standing (i.e., self-supporting) film. Therefore, the carbonaceous current collector is able to maintain its shape without a separate support.
[0076] In the negative electrode for a secondary battery according to one embodiment of the present disclosure, a lithium-based material may be loaded in the carbonaceous current collector. In particular, as the lithium metal migrates during the charge / discharge cycle of the secondary battery, at least a portion of the lithium metal may be loaded in the pores of the carbonaceous current collector.
[0077] In the secondary battery negative electrode according to one embodiment of the present disclosure, the thickness of the porous polymer layer may be 6-20 μm, or 8-12 μm. When the thickness of the porous polymer layer satisfies the above defined range, the elongation, tensile strength and elastic force of the secondary battery negative electrode may be improved.
[0078] In the negative electrode for secondary batteries according to one embodiment of the present disclosure, the porous polymer layer may include polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, or two or more thereof. However, the porous polymer layer is not limited to the materials listed above, and those skilled in the art can select and use various materials not described in the specification.
[0079] In the secondary battery negative electrode according to one embodiment of the present disclosure, the thickness of the lithium-based material layer may be 10-80 μm, 10-60 μm, 20-60 μm, 20-40 μm or 30-50 μm. When the thickness of the lithium-based material layer satisfies the above-defined range, a sufficient level of negative electrode capacity can be ensured.
[0080] In another aspect of the present disclosure, a method for manufacturing a negative electrode for a secondary battery is provided, the method comprising the following steps: stacking a carbonaceous current collector, a porous polymer layer having at least one through-hole on at least one surface of the carbonaceous current collector, and a lithium-based material layer on the upper surface of the porous polymer layer to form a stack; and compressing the stack through a pressing process.
[0081] In the method for manufacturing a negative electrode for a secondary battery according to one embodiment of the present disclosure, the compression step may be performed at a temperature of 180° C. or less, 150° C. or less, or 120° C. or less, at 20-60° C., or at a room temperature of 20-30° C. When the compression step is performed within the above-defined temperature range, it is possible to prevent the melting of a lithium-based material such as lithium metal, suppress the formation of an oxide layer that acts as a resistor in the lithium-based material, and prevent the melting of lithium during the manufacturing process.
[0082] In a method for manufacturing a negative electrode for a secondary battery according to one embodiment of the present disclosure, the compression step may be performed in a dry environment, such as a drying chamber. For example, the compression step may be performed in an environment where the dew point is maintained at below -10°C, below -30°C, or below -45°C. When such conditions are met, contamination of the surface of the lithium-based material, such as the reaction of the lithium-based material with water and the generation of a lithium hydroxide layer, may be suppressed.
[0083] In the method for manufacturing a negative electrode for a secondary battery according to one embodiment of the present disclosure, in the compression step, the lithium-based material layer and the carbonaceous current collector may be attached to each other through a through hole formed in the porous polymer layer. The lithium-based material layer is deformed by compression, introduced into the through hole, and contacts and attaches to the carbonaceous current collector layer.
[0084] In yet another aspect of the present disclosure, a secondary battery is provided, comprising: a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte, wherein the negative electrode is the negative electrode for a secondary battery according to the present disclosure.
[0085] According to one embodiment of the present disclosure, the secondary battery may be a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium sulfur battery, a lithium polymer secondary battery, a lithium ion polymer secondary battery, and the like.
[0086] According to one embodiment of the present disclosure, the positive electrode may include: a positive electrode current collector; and a positive electrode active material layer formed on at least one surface of the positive electrode current collector.
[0087] In general, the thickness of the positive electrode collector may be about 3-500 μm. There are no particular restrictions on the positive electrode collector, as long as it has high conductivity and does not cause any chemical changes in the corresponding battery. Specific examples of the positive electrode collector include stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode collector may have fine surface irregularities formed on its surface to increase the adhesion of the positive electrode active material. For example, the positive electrode collector may have various shapes such as a film, a sheet, a foil, a net, a porous body, a foam or a non-woven fabric.
[0088] The positive electrode active material layer may include a positive electrode active material, a conductive material, and a binder polymer.
[0089] The positive electrode active material may include sulfur (S). Herein, such a sulfur-containing material is referred to as a 'sulfur compound'. For example, the sulfur compound may include any sulfur-containing compound that can be formed by reduction of inorganic sulfur (S8) or oxidation of lithium sulfide (Li2S). More specifically, the sulfur compound may include inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , x is an integer, 2≤x≤8), disulfide compounds, carbon-sulfur polymers ((C2S y ) n , y=2.5-50, n≥2), or two or more thereof.
[0090] Preferably, the positive electrode active material may be a sulfur-carbon composite material. The sulfur-carbon composite material may include: a porous carbonaceous material; and a sulfur compound supported in / on at least one of the pores and the outer surface of the porous carbonaceous material.
[0091] The porous carbonaceous material is not particularly limited as long as it is a porous material made of carbon and can support the sulfur compound as a positive electrode active material, provide a framework capable of uniformly and stably fixing the sulfur compound, and improve the conductivity of the positive electrode.
[0092] In general, the porous carbonaceous material can be obtained by carbonizing a precursor made of various carbonaceous materials. The porous carbonaceous material comprises irregular holes inside it, wherein the average pore size of the holes is 1-200 nm, and relative to the total volume of the porous carbonaceous material, the porosity is 10-90 volume %. When the average pore size is less than the above-defined scope, the pore size is only at the molecular level, so the porous carbonaceous material cannot load sulfur. On the contrary, when the average pore size is greater than the above-defined scope, the porous carbonaceous material shows low mechanical strength, and is therefore not suitable for electrode manufacturing process.
[0093] Here, the 'average pore size' can be determined by any method known to those skilled in the art for determining the pore size of a porous material, and there is no particular limitation on the method. For example, the pore size can be determined by scanning electron microscopy (SEM), field emission electron microscopy, laser diffraction or BET (Brunol-Emmett-Teller) method. For example, the pore size can be determined by laser diffraction using a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT 3000). In addition, the pore size can be determined by the BET method, for example, by using a BELSORP series analyzer available from BEL Japan Co., Ltd., but is not limited thereto.
[0094] The term 'porosity' refers to the ratio of the volume occupied by pores in a structure to the total volume, expressed in the unit of '%', and can be used interchangeably with terms such as void ratio, porosity, etc. According to the present disclosure, there is no particular limitation on the measurement of porosity, and for example, the porosity can be determined by a BET method or a mercury intrusion method using nitrogen gas and according to ASTM D-2873.
[0095] The porous carbonaceous material is not particularly limited in its shape, and any shape conventionally used for lithium-sulfur batteries may be used, including spherical, rod-like, needle-like, sheet-like, tubular, or block-like shapes without particular limitation.
[0096] Any porous carbonaceous material can be used as long as it has a porous structure or a high specific surface area and is conventionally used in the art. Specific examples of the porous carbonaceous material include at least one selected from the group consisting of: graphite; graphene; carbon black, such as Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNT), such as single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), etc.; carbon fibers, such as graphite nanofibers (GNF), carbon nanofibers (CNF) and activated carbon fibers, etc.; graphite, such as natural graphite, artificial graphite, expanded graphite, etc.; and activated carbon, but not limited thereto. Preferably, the porous carbonaceous material can be a carbon nanotube.
[0097] There is no particular limitation on the method for preparing the sulfur-carbon composite material, and any conventional method known to those skilled in the art may be used. For example, a method may be used that includes simply mixing sulfur with a porous carbonaceous material and heat treating the mixture to form a composite material.
[0098] The positive electrode active material may further include at least one selected from the group consisting of transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, and alloys of sulfur and these elements.
[0099] The transition metals may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., the IIIA group elements may include Al, Ga, In, Ti, etc., and the IVA group elements may include Ge, Sn, Pb, etc.
[0100] The amount of the sulfur-carbon composite material used may be 50% by weight or more relative to the total weight of the positive electrode. In particular, the amount of the sulfur-carbon composite material used may be 80% by weight or more, 90% by weight or more, or 95% by weight or more relative to the total weight of the positive electrode active material. In particular, the amount of the sulfur-carbon composite material used may be 80-100% by weight, more particularly 85-99% by weight, 90-99% by weight, 95-98% by weight, 95-97% by weight, or 96% by weight relative to the total weight of the positive electrode active material.
[0101] According to one embodiment of the present disclosure, the binder polymer retains the positive active material in the positive current collector and organically interconnects the positive active material particles themselves to enhance the binding force therebetween, and any binder polymer known to those skilled in the art may be used.
[0102] For example, the adhesive polymer may include any one selected from the group consisting of: polyacrylic acid (PAA); fluororesin adhesives, including polyvinylidene fluoride (PVDF), polyvinylidene fluoride polymers containing at least one vinylidene fluoride unit as a repeating unit, polytetrafluoroethylene (PTFE), or two or more thereof; rubber adhesives, including styrene-butadiene rubber (SBR), nitrile rubber or styrene-isoprene rubber; acrylic adhesives; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose or regenerated cellulose; polyol adhesives; polyolefin adhesives, including polyethylene or polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives, or a mixture or copolymer of two or more thereof.
[0103] According to one embodiment of the present disclosure, the content of the binder may be 1-10% by weight relative to the total weight of the positive electrode active material layer. When the content of the binder is less than the above-defined range, the physical properties of the positive electrode may be degraded, resulting in separation of the positive electrode active material and the conductive material. When the content of the binder is greater than the above-defined range, the ratio of the positive electrode active material to the conductive material is relatively reduced, resulting in a decrease in battery capacity. Therefore, it is preferred to determine the appropriate content of the binder within the above-defined range.
[0104] According to one embodiment of the present disclosure, the conductive material is a material for electrically connecting the positive electrode active material and the electrolyte to provide a path for electrons to be conducted to the positive electrode active material. Any conductive material can be used without particular limitation as long as it has conductivity as an electrode forming element physically different from the carbon contained in the sulfur-carbon composite material.
[0105] Specific examples of the conductive material may include: carbon black, such as Super P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon derivatives, such as carbon nanotubes or fullerenes; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder, nickel powder, etc.; or conductive polymers, such as polyaniline, polythiophene, polyacetylene, polypyrrole, etc. Such conductive materials may be used alone or in combination.
[0106] According to one embodiment of the present disclosure, the content of the conductive material may be 1-10% by weight relative to the total weight of the positive electrode active material. When the content of the conductive material is less than the above-defined range, it is not conducive to the electronic conduction between the positive electrode active material and the current collector, resulting in voltage and capacity degradation. On the contrary, when the content of the conductive material is greater than the above-defined range, the proportion of the positive electrode active material is relatively reduced, resulting in a reduction in the total energy (amount of charge) of the battery. Therefore, it is preferred to determine the content of the conductive material within the above-defined range.
[0107] According to one embodiment of the present disclosure, the separator is used to separate or insulate the positive electrode from the negative electrode and allow lithium ions to be transmitted between the positive electrode and the negative electrode, and may include a porous non-conductive material or an insulating material, and any separator may be used without particular limitation as long as it is generally used as a separator for a lithium secondary battery. Such a separator may be an independent member, such as a film, or a coating added to the positive electrode and / or the negative electrode.
[0108] The separator preferably exhibits low resistance to electrolyte ion migration and has excellent wettability with the electrolyte.
[0109] According to one embodiment of the present disclosure, the separator may include a porous substrate. Any porous substrate commonly used in secondary batteries can be used, and a porous polymer film can be used alone or in the form of a laminate. For example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, or a polyolefin porous membrane can be used, but the scope of the present disclosure is not limited thereto.
[0110] Any porous substrate can be used without particular limitation as long as it is a porous substrate generally used for electrochemical devices. For example, the porous substrate may include at least one material selected from the group consisting of polyolefins such as polyethylene or polypropylene; polyesters such as polyethylene terephthalate or polybutylene terephthalate; polyamides; polyacetals; polycarbonates; polyimides; polyetheretherketones; polyethersulfones; polyphenylene oxides; polyphenylene sulfides; polyethylene naphthalate; polytetrafluoroethylene; polyvinylidene fluoride; polyvinyl chloride; polyacrylonitrile; cellulose; nylon; poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); poly(p-phenylenebenzobis[epsilon]); azoles); and polyarylates.
[0111] According to one embodiment of the present disclosure, the thickness of the porous substrate is not particularly limited, but may be 1-100 μm, preferably 5-50 μm. Although the thickness of the porous substrate is not limited to the above-defined range, a thickness much less than the above-defined lower limit results in deterioration of mechanical properties, which may make the separator easily damaged during battery use.
[0112] According to one embodiment of the present disclosure, although there is no particular limitation on the average diameter and porosity of the pores present in the porous substrate, preferably the average diameter and porosity may be 0.001-50 μm and 10%-95%, respectively.
[0113] According to one embodiment of the present disclosure, the separator may further include a porous coating layer formed on at least one surface of the porous substrate and including inorganic particles and an adhesive. There are no particular restrictions on the inorganic particles and adhesive contained in the porous coating layer, as long as they are commonly used in the porous coating layer of separators. In addition, there is no restriction on the preparation method of such a porous coating layer.
[0114] According to one embodiment of the present disclosure, the electrolyte includes a lithium salt as an electrolyte salt and an organic solvent for dissolving the lithium salt.
[0115] There is no particular limitation on the lithium salt as long as it is conventionally used in electrolytes for secondary batteries, such as LiNO3 and LiTFSI. Specific examples of the anion of the lithium salt may include at least one selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C -CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0116] There is no particular limitation on the organic solvent contained in the electrolyte as long as it is a commonly used organic solvent. Typical examples of the organic solvent may include at least one selected from the group consisting of propylene carbonate, ethylene carbonate, dimethyl ether (DME), 1,3-dioxolane (DOL), diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, cyclopentane, γ-butyrolactone, propylene sulfite and tetrahydrofuran.
[0117] Especially, among the carbonate organic solvents, ethylene carbonate or propylene carbonate as cyclic carbonate is a high viscosity organic solvent and can well dissociate the lithium salt in the electrolyte, so it can be preferably used. When such cyclic carbonate is used in the form of a mixture of a suitable ratio with a low viscosity and low dielectric constant linear carbonate such as dimethyl carbonate or diethyl carbonate, it is possible to preferably prepare an electrolyte with high conductivity.
[0118] Optionally, the electrolyte used according to the present disclosure may further include additives contained in conventional electrolytes, such as an overcharge preventer.
[0119] The lithium secondary battery according to one embodiment of the present disclosure can be obtained by inserting a separator between the positive electrode and the negative electrode to form an electrode assembly, introducing the electrode assembly into a bag-shaped, cylindrical, square battery case, etc., and injecting an electrolyte therein. In a variant, the lithium secondary battery can be obtained by stacking the electrode assemblies, wetting the electrode assemblies with an electrolyte, and introducing the resulting product into a battery case, which is then sealed.
[0120] Mode of the Disclosure
[0121] Hereinafter, the present disclosure will be described in more detail with reference to examples. However, the following examples are for illustrative purposes only, and the scope of the present disclosure is not limited thereto.
[0122] Example 1
[0123] First, a lithium metal foil with a thickness of 50 μm as the first lithium metal layer, a polyethylene porous film with a thickness of 10 μm as the first porous polymer layer, a carbon nanotube with a thickness of 10 μm as the carbonaceous current collector, a polyethylene porous film with a thickness of 10 μm as the second porous polymer layer, and a lithium metal foil with a thickness of 50 μm as the second lithium metal layer are prepared and stacked in sequence, and then the resulting stack is compressed by a pressing (rolling) process at 25°C to obtain a negative electrode. Here, the first porous polymer layer and the second porous polymer layer are provided with at least one through hole, and the area occupied by the through hole formed in the first porous polymer layer and the second porous polymer layer is 50% relative to the total area of the porous polymer layer, and the diameter of the through hole is 1.9 cm.
[0124] Comparative Example 1
[0125] A lithium metal foil with a thickness of 100 μm was prepared as a negative electrode.
[0126] Comparative Example 2
[0127] First, a lithium metal foil with a thickness of 50 μm as a first lithium metal layer, a carbon nanotube film with a thickness of 10 μm as a carbonaceous current collector, and a lithium metal foil with a thickness of 50 μm as a second lithium metal layer are prepared and stacked in sequence, and then the resulting stack is compressed by a pressing (rolling) process at 25°C to obtain a negative electrode.
[0128] Example 2
[0129] <Preparation of negative electrode>
[0130] The same negative electrode as that obtained in Example 1 was prepared.
[0131] <Manufacturing of lithium-sulfur batteries>
[0132] A sulfur-carbon composite material containing sulfur supported in carbon nanotubes was prepared as a positive electrode active material. Here, the weight ratio of the carbon nanotubes to the sulfur was 1:3. Then, polyacrylic acid (PAA) as a binder and carbon fibers as a conductive material were mixed therewith to prepare a positive electrode slurry. Here, the weight ratio of the positive electrode active material, the conductive material and the binder was 88:5:7.
[0133] The resulting slurry was coated on an aluminum foil using a Matis coating device, dried at 50° C. for 24 hours, and then pressed to obtain a positive electrode.
[0134] As an electrolyte, a mixed solution containing 0.75 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt % lithium nitrate (LiNO 3 ) dissolved in an organic solvent containing 1,3-dioxolane and dimethyl ether (DOL:DME=1:1 (volume ratio)) was prepared.
[0135] The positive electrode and the negative electrode were opposed to each other, a polyethylene separator having a thickness of 16 μm and a porosity of 46% was inserted between the two electrodes, the resultant was housed in a pouch-shaped battery case, and the electrolyte was injected therein to obtain a lithium-sulfur battery.
[0136] Comparative Example 3
[0137] A lithium-sulfur battery was obtained in the same manner as in Example 2 except that the negative electrode prepared in Comparative Example 1 was used.
[0138] Test Example 1: Tensile Strength Test
[0139] Tensile strength was determined according to ASTM D-412 B.
[0140] Each electrode according to Example 1 and Comparative Examples 1 and 2 was formed into a specimen conforming to ASTM D-412 B. Then, a tensile strength test was performed using a universal testing machine (UTM) and each specimen using a 100N load cell.
[0141] While applying a strain of 0.01 mm / sec, the maximum stress value was measured to obtain the tensile strength. The results are shown in Table 1 below.
[0142]
[0143] Figure 3 is a graph showing the tensile strength test results of the negative electrode according to Example 1, Figure 4 3 is a graph showing the results of a tensile strength test of negative electrodes according to Comparative Examples 1 and 2.
[0144] Refer to Table 1. Figure 3 and Figure 4 , it can be seen that the tensile strength of Example 1 is significantly increased compared with Comparative Example 1. Since the negative electrode according to Comparative Example 1 contains only lithium metal foil, it has low rigidity and significantly elongates under strain. Compared with Comparative Example 2, Example 1 shows a significantly increased elongation length at break. This is because Example 1 contains a porous polymer layer, so the elongation is increased.
[0145] Test Example 2: Capacity Retention Test
[0146] Figure 5 : is a graph showing the single cell performance evaluation results of the lithium-sulfur batteries according to each of Example 2 and Comparative Example 3.
[0147] The lithium-sulfur batteries according to each of Example 2 and Comparative Example 3 were charged (0.3C, constant current (CC) mode) and discharged (0.5C, CC mode) at 25° C., and the discharge capacity retention rate was calculated according to the following formula:
[0148] Discharge capacity retention rate (%) = [(discharge capacity at the first cycle - discharge capacity at the nth cycle) / discharge capacity at the first cycle] × 100
[0149] The lithium-sulfur battery according to Example 2 showed a capacity retention rate of more than 80% even at the 250th cycle, but the lithium-sulfur battery according to Comparative Example 3 showed a rapid decrease in capacity retention rate before the 100th cycle.
[0150] The present disclosure has been described in detail. However, it should be understood that the detailed description and specific examples, while indicating preferred embodiments of the present disclosure, are given only as examples, as various changes and modifications within the scope of the present disclosure will become apparent to those skilled in the art from this detailed description.
Claims
1. A negative electrode for a secondary battery, the negative electrode comprising: Carbon current collector; A porous polymer layer disposed on at least one surface of the carbonaceous current collector; and A lithium-based material layer is disposed on an upper surface of the porous polymer layer. 2 . The negative electrode for a secondary battery according to claim 1 , wherein the lithium-based material layer contains at least one of lithium metal and lithium alloy. 3 . The negative electrode for a secondary battery according to claim 1 , wherein the lithium-based material layer is a lithium metal layer. 4 . The negative electrode for a secondary battery according to claim 1 , wherein the porous polymer layer has at least one through-hole formed therein, and the carbonaceous current collector and the lithium-based material layer are attached to each other through the through-hole. 5 . The negative electrode for a secondary battery according to claim 4 , wherein the through holes formed in the porous polymer layer occupy an area equivalent to 15% to 60% with respect to the total area of the porous polymer layer. 6 . The negative electrode for a secondary battery according to claim 4 , wherein the diameter of the through-holes formed in the porous polymer layer is 0.5 to 3 cm. 7 . The negative electrode for a secondary battery according to claim 1 , wherein the porous polymer layer is provided on both surfaces of the carbonaceous current collector.
8. The negative electrode for a secondary battery according to claim 1, wherein the specific surface area of the carbonaceous current collector is 50 m 2 / g or above.
9. The negative electrode for a secondary battery according to claim 1, wherein the surface density of the carbonaceous current collector is 100 g / m 2 the following. 10 . The negative electrode for a secondary battery according to claim 1 , wherein the carbonaceous current collector layer comprises graphite, graphene, carbon nanotube (CNT), graphite nanofiber (GNF), carbon nanofiber (CNF), activated carbon fiber (ACF), or two or more thereof.
11. The negative electrode for a secondary battery according to claim 1, wherein the porous polymer layer comprises polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, or two or more thereof.
12. A method for manufacturing a negative electrode for a secondary battery, the method The following steps are involved: stacking a carbonaceous current collector, a porous polymer layer having at least one through-hole on at least one surface of the carbonaceous current collector, and a lithium-based material layer on an upper surface of the porous polymer layer to form a laminate; and The laminate is compressed through a pressing process. 13 . The method for manufacturing a negative electrode for a secondary battery according to claim 12 , wherein the lithium-based material layer contains at least one of lithium metal and lithium alloy. 14 . The method for manufacturing a negative electrode for a secondary battery according to claim 12 , wherein the lithium-based material layer is a lithium metal layer. 15 . The method for producing a negative electrode for a secondary battery according to claim 12 , wherein the compressing step is performed at a temperature of 180° C. or lower. 16 . The method of manufacturing a negative electrode for a secondary battery according to claim 12 , wherein in the compressing step, the lithium-based material layer and the carbonaceous current collector are attached to each other through through holes formed in the porous polymer layer. 17 . A secondary battery comprising: a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte, wherein the negative electrode is the negative electrode defined in any one of claims 1 to 11 .
